Effectiveness of mayer’s problem solving model with visual representation teaching strategy in enhancing year four pupils’ mathematical problem solving ability / Sharmilla Palanisamy - Sharmilla, Palanisamy (2020)
This study aims to determine the effectiveness of Mayer’s problem solving Model with Visual Representation (MMVR) teaching strategy in enhancing Year 4 students’ mathematical problem solving ability in Klang Valley, and its interaction with gender. A quasi-experimental research design was employed in this study. A sample of 203 Year 4 students consisting of 101 males and 102 females from a private school in Klang Valley were drawn using a convenient sampling technique with two classes assigned as the experimental groups namely Mayer’s problem solving Model (MM) and MMVR groups, and the other one as the control group. The MM group was given Mayer’s problem solving Model (MM) teaching strategy treatment, while the MMVR group was given Mayer’s problem solving Model with Visual Representation (MMVR) teaching strategy treatment respectively. The control group on the other hand did not receive any treatment. Students’ mathematical problem solving ability before and after treatments was measured using an instrument called Mathematical Problem Solving Ability Test (MPSAT). The study found that MMVR teaching strategy was effective in improving students’ mathematical problem solving ability because the paired samples statistics for pretest and posttest scores of problem solving ability for MMVR group shows the mean scores of MPSAT in MMVR group for pretest (M = 75.41, SD = 3.70) and posttest (M = 115.86, SD = 6.47) is different, with statistically significant mean increase for mathematical problem solving ability in MMVR group, t (57) = 41.05, p < .0005. Also, the results of one-way ANCOVA analysis reveals that there is a statistically significant difference in the mean of the posttest score in MPSAT between the three groups, F (2, 171) = 291.44, p < .0005 (Ƞp2 = .77, observed power = 1), with the adjusted means of posttest scores of MPSAT for MM, MMVR and Control groups were 105.84 (SE = .94), 116.14 (SE = .93), and 85.94 (SE = .89) respectively. However, the study were not able to show that there is significant interaction between problem solving teaching strategy and gender on students’ mathematical problem solving ability because the result of two-way ANCOVA analysis indicates that the interaction effect between gender and the groups on mathematical problem solving ability was not statistically significant, F (2, 169) = .018, p = .98 (p > .05), with a minimal effect size (Ƞp2= .00022). The findings suggest that MMVR teaching strategy can be an effective approach in improving students’ mathematical problem solving ability. The study suggests that teachers should incorporate Mayer’s problem solving Model with Visual Representation teaching strategy into their lesson to help students improve their mathematical problem solving ability.